Magnetic field and vibration effects on the onset of thermal convection in a grade fluid permeated anisotropic porous module. (May 2019) - Purusothaman, A.; Sekar, R. Chandra Guru; Murugesan, K.
Graphical abstract: Highlights: Investigating the magnetic field and vibration effects on convection simulation in porous module. Linear stability analysis is performed using Floquet theory. Mathieu's functions and stability charts are used to evaluate the stable and unstable regions. The conditions of convective instability onset are achieved in the parameter space. Influence of the magnetic field ensures a stable environment subject to gravity modulation. Abstract: A study of thermo–vibrational convective instability in an infinitely extended flat anisotropic porous module, permeated by a second-grade fluid and heated from below is investigated depending on an externally imposed magnetic field. The Floquet hypothesis is applied to govern the onset condition within the background of linear stability theory by means of normal mode assumption. The present investigation is focused on the small amplitude mechanical vibration and the results are found by means of Mathieu's functions and its stability charts. Special emphasis is given to examine the effects on anisotropies in permeability and thermal diffusivity of the porous module along the transverse direction. The emerging instabilities by means of the synchronous and subharmonic modes and the exact changeover point among them are examined for the different governing parameters. It is revealed that the externally imposed magnetic force has a stabilizing impact and hence a drop in flow moments.